Modalities, uses and presence of fiction as a creative resource in radio advertising - Arcos Foix, Núria; Perona Páez, Juan José (Anàlisi, 2011)
After defining what can be considered fiction in radio advertising and coining three different fictional modalities –dramatized, narrated and illustrative or media testimonial–, this article studies and analyzes how frequently fiction and each of its modalities are found in conventional radio spots, as well as their specificity according to the advertised product or service and the type of advertising (commercial or non-commercial). Results demonstrate that, despite its communicative and seductive potential when it comes to constructing eminently persuasive messages, fiction is a hardly used creative resource, which appears in less than a third of the advertisements.